Pelvic aggressive fibromatosis masquerading as a uterine fibroid: a diagnostic challenge - A. K., Asma; P. K., Sathiamma; Yusuf, Rafeek; A., Muneer (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
An invasive pelvic mass in a young female presents a diagnostic challenge, as a variety of benign and malignant conditions can contribute to such findings. One rare but significant cause of an invasive pelvic mass are desmoid tumours (also called aggressive fibromatosis) benign, slowly growing fibroblastic neoplasms with no metastatic potential but a propensity for local recurrence, even after complete surgical resection. We report a case of pelvic aggressive fibromatosis - a young woman who presented with gynaecological symptoms and was found to have a large invasive pelvic mass that closely mimicked a uterine fibroid or gynaecological malignancy on clinical examination and imaging. Surgical management was undertaken due to the extent of the lesion and diagnostic uncertainty. Definitive diagnosis was established only on histopathological examination, supported by immunohistochemistry, confirming desmoid fibromatosis. This case underscores the importance of including desmoid fibromatosis in the differential diagnosis of invasive pelvic masses in young females. It also highlights the limitations of imaging in distinguishing benign from malignant pelvic tumours and emphasises the pivotal role of histopathology and immunohistochemistry in establishing the diagnosis and guiding appropriate multidisciplinary management.